Reconceptualising inclusion as participation: Neoliberal buck-passing or strategic by-passing?. Issue 4 (3rd July 2016) - Graham, Linda J.
ABSTRACT: This paper investigates increases in the identification of special educational needs in the New South Wales (NSW) government school system over the last two decades, which are then discussed with senior public servants working within the NSW Department of Education and Communities (DEC). Participant narratives indicate deep structural barriers to inclusion that are perpetuated by the discourses and practices of regular and special education. Despite policies that speak of 'working together' for 'every student' and 'every school', students who experience difficulty in schools and with learning often remain peripheral to the main game, even though their number is said to be increasing. There is, however, some positive progress being made. Findings suggest that key policy figures within the NSW DEC are keenly aware of the barriers and have adopted alternative strategies to drive inclusion via a new discourse of 'participation' which is underpinned by the linking of student assessment and the resourcing of schools.